Nitrogen and sulfur isotopes predict variation in mercury levels in Arctic seabird prey. (October 2018) - Góngora, Esteban; Braune, Birgit M.; Elliott, Kyle H.
Abstract: Mercury (Hg) biotransformation and biomagnification are processes that affect Hg burdens in wildlife. To interpret variation in Hg in seabird eggs, used as Hg bioindicators in the Arctic, it is important to understand how Hg biomagnifies through the food web. We evaluated the use of δ 34 S, along with other commonly used stable isotope signatures (δ 15 N and δ 13 C), for the determination of possible sources of Hg in an Arctic food web (56 individuals of 15 species of fish and invertebrates). Hg correlated with δ 34 S ( R 2  = 0.72). When the combined effects of δ 34 S and δ 15 N were considered in mixed-effects models, both δ 34 S and δ 15 N together described Hg patterns in Arctic food webs better than either isotope alone. Our results demonstrate the usefulness of δ 34 S to account for variation in Hg among marine animals and to study the possible underlying effects that MeHg production may have on Hg pathways in Arctic ecosystems. Graphical abstract: Highlights: Stable isotopes were used to determine sources of Hg variation in Arctic food webs. δ 34 S enhanced the interpretation of Hg variation in marine fish and invertebrates. We suggest that δ 34 S be incorporated into Hg monitoring programs.